+0  
 
0
446
1
avatar

-13x -3x² was ist dao´von die lösung ?

 19.06.2015

Beste Antwort 

 #1
avatar+14537 
+3

Guten Abend Anonymous,


1.)   -13x -3x² = -x*(13+3x)


2.)  -13x -3x² = 0       |  * (-1)


         13x + 3x² = 0


          x *( 13+3x ) = 0           =>      x1 = 0       ;      13+3x =0     


                                                                            =>  3x = -13   =>   x = $${\mathtt{\,-\,}}{\frac{{\mathtt{13}}}{{\mathtt{3}}}}$$


Gruß radix !

 19.06.2015
 #1
avatar+14537 
+3
Beste Antwort

Guten Abend Anonymous,


1.)   -13x -3x² = -x*(13+3x)


2.)  -13x -3x² = 0       |  * (-1)


         13x + 3x² = 0


          x *( 13+3x ) = 0           =>      x1 = 0       ;      13+3x =0     


                                                                            =>  3x = -13   =>   x = $${\mathtt{\,-\,}}{\frac{{\mathtt{13}}}{{\mathtt{3}}}}$$


Gruß radix !

radix 19.06.2015

25 Benutzer online

avatar